Facility-Based treatment of under five diarrhoea in Cross River State: A clinical audit - Meremikwu M; Udoh E; Esu E; Chibuzor M; Meremikwu M; Oduwole O; Arikpo D; Odey F (Nigerian Journal of Paediatrics, 2024)
Introduction: Diarrhoea is the second leading cause of under-five mortality globally and ranks second among the top 10 priority child health problems in Nigeria. The World Health Organization (WHO) has recommended some cost-effective, evidence- based interventions for diarrhoea case management. It is needful to evaluate the current practice in the treatment of diarrhoea in under-fives in health facilities in the country.